2017
DOI: 10.1080/01658107.2017.1334218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Fat Distribution in Idiopathic Intracranial Hypertension Using Dual-Energy X-ray Absorptiometry Scanning

Abstract: Idiopathic intracranial hypertension (IIH) is strongly associated with obesity. We aimed to utilise dual-energy X-ray absorptiometry (DEXA) to characterise fat distribution, and to evaluate change in fat mass and distribution following weight loss. IIH patients (n = 24) had a similar fat distribution to body mass index (BMI)– and gender-matched obese controls (n = 47). In the IIH cohort, truncal fat mass correlated with lumbar puncture pressure. Weight loss in IIH patients resulted in a significant reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“… 28 , 29 , 30 Centripetal fat predominance has been identified in IIH and correlates with intracranial pressure. 31 Whether obesity is causal in IIH, or if it represents a comorbidity driven by the underlying metabolic disease state, is unclear. However, weight loss is associated with resolution of IIH.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 , 30 Centripetal fat predominance has been identified in IIH and correlates with intracranial pressure. 31 Whether obesity is causal in IIH, or if it represents a comorbidity driven by the underlying metabolic disease state, is unclear. However, weight loss is associated with resolution of IIH.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, truncal fat mass and higher BMI has been associated with more severe visual These authors contributed equally: B.B. Bruce, A. Sinclair loss [4,5]. Obesity affects 30.4% of British women and 38.2% of American women [6] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study the gold standard dual-energy X-ray absorptiometry (DEXA) scanning technique was used to evaluate fat mass and distribution in IIH patients. In this study the authors found instead that IIH patients have a similar centripetal distribution of fat mass to patients with simple obesity [68]. These results raise the question whether it is the type of adipose tissue or its location that is of relevance for IIH.…”
Section: Iih Pathophysiologymentioning
confidence: 65%